2008
DOI: 10.1037/a0013036
|View full text |Cite
|
Sign up to set email alerts
|

Teacher key opinion leaders and mental health consultation in low-income urban schools.

Abstract: Diffusion theory posits that information is disseminated throughout a social network by the persuasion of key opinion leaders (KOLs). This study examined the relative and combined influence of peer-identified KOL teachers (n = 12) and mental health providers (n = 21) on classroom teachers' (n = 61) self-reported use of commonly recommended classroom practices for children with attention-deficit/hyperactivity disorder in 6 low-income urban African American communities, relative to teachers (n = 54) at 4 matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(92 citation statements)
references
References 23 publications
4
88
0
Order By: Relevance
“…When implementing interventions that require a longer timeframe, it will be especially important to develop methods of measuring short-term progress and of feeding back these results to implementers and other school staff. In addition, an understanding of the social nature of the implementation process (Rogers, 2003) and the importance of teachers as key opinion leaders (Atkins et al, 2008) should be an important consideration in garnering support from school personnel.…”
Section: Discussionmentioning
confidence: 99%
“…When implementing interventions that require a longer timeframe, it will be especially important to develop methods of measuring short-term progress and of feeding back these results to implementers and other school staff. In addition, an understanding of the social nature of the implementation process (Rogers, 2003) and the importance of teachers as key opinion leaders (Atkins et al, 2008) should be an important consideration in garnering support from school personnel.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 The literature promotes the idea of EBT champions within organizations for implementing and sustaining EBTs. 54 Although not the focus of this paper, the field would benefit from additional research on how to build champions within organizations, or other internal network change agents, 55 for promoting and advancing EBTs.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of iterative studies, we have identified teacher-referred children in early elementary grades exhibiting disruptive behaviors that impair classroom functioning and interfere with academic progress. Community mental health providers, parent advocates, and peer-identified teacher key opinion leaders (M. S. Atkins et al, 2008) together receive training and supervision in the implementation of evidence-based tools for the key empirical classroom and home predictors of children's learning. This ongoing work links universal (classroom-wide) and targeted (services for high need youth) levels to redefine mental health goals, mobilize natural and indigenous resources, and capitalize on the inherent capacity of natural settings to promote children's healthy development (M. Atkins et al, 2006.…”
Section: Targetedmentioning
confidence: 99%